miRNA Involvement in Cerebral Ischemia-Reperfusion Injury - Neag, Maria-Adriana; Mitre, Andrei-Otto; Burlacu, Codrin-Constantin; Inceu, Andreea-Ioana; Mihu, Carina; Melincovici, Carmen-Stanca; Bichescu, Marius; Buzoianu, Anca-Dana (Frontiers in Neuroscience, 2022)
Cerebral ischemia reperfusion injury is a debilitating medical condition, currently with only a limited amount of therapies aimed at protecting the cerebral parenchyma. Micro RNAs (miRNAs) are small, non-coding RNA molecules that via the RNA-induced silencing complex either degrade or prevent target messenger RNAs from being translated and thus, can modulate the synthesis of target proteins. In the neurological field, miRNAs have been evaluated as potential regulators in brain development processes and pathological events. Following ischemic hypoxic stress, the cellular and molecular events initiated dysregulate different miRNAs, responsible for long-terming progression and extension of neuronal damage. Because of their ability to regulate the synthesis of target proteins, miRNAs emerge as a possible therapeutic strategy in limiting the neuronal damage following a cerebral ischemic event. This review aims to summarize the recent literature evidence of the miRNAs involved in signaling and modulating cerebral ischemia-reperfusion injuries, thus pointing their potential in limiting neuronal damage and repair mechanisms. An in-depth overview of the molecular pathways involved in ischemia reperfusion injury and the involvement of specific miRNAs, could provide future perspectives in the development of neuroprotective agents targeting these specific miRNAs.